Analisis Potensi Pengembangan Kawasan Desa Wisata Di Pulau Galang - Lawita, Nadia Fathurrahmi; Ulfah, Mutia; Sabrina, Nova; Putri, Ancala Laras; Oktarici, Eddo Nanda; Latifa, Nurul; Nasution, Lala Zakiya; Maharani, Fazila; Ningsih, Fifi Suria; Dillah, Shalsha (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This research aims to identify the tourism potential of Galang Island. The assumption underlying this research is that the development of a Tourism Village area can increase the overall tourism attractiveness of Galang Island and provide economic and social benefits for the local community. This research uses a case study approach because it is in accordance with the nature of research that centers on observing specific phenomena and contexts so that researchers can collect data thoroughly through observation, interviews, and document analysis related to the development of the Tourism Village area on the island. This research found that Galang Island has significant tourism potential with community support, but the challenges of infrastructure and economic empowerment still need to be overcome and require further research for tourism diversification and collaboration with the private sector.